Mapping ideas around the table - Zaphiris, Panayiotis; Ioannou, Andri; Loizides, Fernando (My University, 2012)
This paper reports work in progress regarding the design, development and evaluation of a surface computing application in support of collaborative problem-based learning (PBL). The domain-independent application, so called Ideas Mapping, supports idea generation, collaborative decision making and group artifact construction — all of which are important aspects of collaborative PBL. During idea generation, Ideas Mapping replicates physical post-it notes on a multi-touch tabletop. Additional functionality supports student collaboration and interaction around the organization of ideas into thematic categories associated with the problem at hand. We report on the functionality of the application which was designed and developed following a user-centered approach. We also report preliminary results from a case study conducted to examine the affordances of the application for collaborative PBL.
Keywords: CSCL; CSCW; Collaborative learning; Surface computing; Multitouch interactive tabletops; Collaborative PBL; Interaction design